Self-isolation is depicted in the works of artist Latif Al-Samhan - Raafat Riyad AbdulWahed (Basrah Arts Journal, 2024)
The researcher dealt with the study, (Manifestations of self-isolation in the works of the artist Latif Al-Samhan). The researcher studied the topic of self-isolation psychologically and philosophically, and revealed the sources of this duality throughout the history of fine art, specifically drawing, as it contained four chapters. The first chapter dealt with (the methodological framework of the research) if it included the research problem. Which the researcher summarized by asking what were the (manifestations of self-isolation), as the problem included research into the artistic style followed by the artist, painter Latif Al-Samhan, and the extent of its influence, and then the importance of the research and the need for a research goal, the limits of the research, and the definition of terms, as well as the procedural definitions that agreed with the researcher’s point of view. The second chapter: which represents the theoretical framework, as it contains two sections, the first section Which represents the theoretical framework, he had discussed, firstly: the concept of self-isolation, secondly: Socrates’ theory, and thirdly: isolation according to (Feuerbach). Fourth: The ego, isolation, and the social spirit. Fifth: (Freud’s theory). The second section: Isolation and its impact on plastic art. First: Isolation in European art. The second chapter concluded by reviewing the indicators of the theoretical framework to benefit from here in terms of building the research tool, analyzing its sample, and presenting and discussing previous studies. In the third chapter, it is devoted to research procedures, in which it reviews the definition of the “research community,” selecting samples from the community as a sample, and determining the methodology used in the research. The fourth chapter: research results, conclusions, recommendations and proposals.